Principios éticos en la investigación biomédica - Piscoya-Arbañil, Julio Alberto (2019)
It is discussed the ethical principles applied to the research, consent, the acceptance of community, disclosure of information, communication, publication of results andreduction of damage, social customs, cultural differences, the confidentiality, incompatibility of interests and others that will help to raise research models in accordance with theethical principles around the world. It is concluded that the primary purpose of medical research involving human subjects is to understand the causes, course and effects of diseases and improve preventive, diagnostic and therapeutic interventions; and, this, with greater reason should motivate us to the constant up to date of the standards that govern performance in biomedical research in our community and the world.